"I Believe I Can and Should": Self‐efficacy, Normative Beliefs and Conservation Behavior. (5th May 2022) - Pradhananga, Amit K.; Davenport, Mae A.
Abstract: This study examines the social‐psychological drivers of conservation action among landowners in Minnesota. In particular, we apply an integrated norm activation theory to understand landowner conservation behavior. Data were collected through a self‐administered mail survey of 3, 000 landowners in La Crescent and Reno Watersheds in Southeastern Minnesota and analyzed using structural equation modeling. Study findings show that landowners' conservation action is driven by their feelings of personal obligation, and beliefs about whether one is capable of taking actions to influence outcomes (i.e., self‐efficacy). Landowners who feel a sense of personal obligation and believe that their actions can make a difference are more likely to take conservation actions. Further, landowners who believe it is their personal responsibility to protect water and perceive social expectations are more likely to develop feelings of personal obligation. Importantly, this study highlights the role of self‐efficacy as an activator of personal norm, as well as a driver of conservation behavior. Our study suggests that strategies that appeal to landowners' sense of personal responsibility and self‐expectations, promote conservation action as a social norm, and build landowners' self‐efficacy or confidence in their ability to make a difference, are likely to be successful.